Spectroscopic and Computational Study of a Nonheme Iron Nitrosyl Center in a Biosynthetic Model of Nitric Oxide Reductase1. Issue 9 (31st January 2014) - Chakraborty, Saumen; Reed, Julian; Ross, Matthew; Nilges, Mark J.; Petrik, Igor D.; Ghosh, Soumya; Hammes‐Schiffer, Sharon; Sage, J. Timothy; Zhang, Yong; Schulz, Charles E.; Lu, Yi
Abstract A major barrier to understanding the mechanism of nitric oxide reductases (NORs) is the lack of a selective probe of NO binding to the nonheme FeB center. By replacing the heme in a biosynthetic model of NORs, which structurally and functionally mimics NORs, with isostructural ZnPP, the electronic structure and functional properties of the FeB nitrosyl complex was probed. This approach allowed observation of the first S=3/2 nonheme {FeNO}7 complex in a protein‐based model system of NOR. Detailed spectroscopic and computational studies show that the electronic state of the {FeNO}7 complex is best described as a high spin ferrous iron (S=2) antiferromagnetically coupled to an NO radical (S= 1/2) [Fe2+‐NO.]. The radical nature of the FeB‐bound NO would facilitate NN bond formation by radical coupling with the heme‐bound NO. This finding, therefore, supports the proposed trans mechanism of NO reduction by NORs.